Diffusion tensor imaging in radiosurgical callosotomy - Moreno-Jiménez, Sergio; San-Juan, Daniel; Lárraga-Gutiérrez, José M.; Celis, Miguel A.; Alonso-Vanegas, Mario A.; Anschel, David J. (Seizure (London, England), 2012)
Callosotomy by radioneurosurgery induces slow and progressive axonal degeneration of white matter fibers, a key consequence of neuronal or axonal injury (radionecrosis). However, the acute effects are not apparent when using conventional MRI techniques. Diffusion tensor imaging (DTI) during the first week following radioneurosurgical callosotomy allowed evaluation of these microstructural changes. The present report details that the use of sequential DTI to evaluate axonal degeneration following radioneurosurgical callosotomy in a patient normalized with the data of six healthy subjects. We describe a 25-year old woman with symptomatic generalized epilepsy who underwent a radioneurosurgical callosotomy using LINAC (Novalis® BrainLAB). DTI was acquired at the baseline, 3 and 9 months and showed a progressive decrease of the fractional anisotropy values in the irradiated areas compared to the controls that could be interpreted as a progressive disconnection of callosal fibers related to the outcome.